The Flipped MOOC: Using Gamification and Learning Analytics in MOOC Design—A Conceptual Approach - Roland Klemke (Education Sciences, 2018)
Recently, research has highlighted the potential of Massive Open Online Courses (MOOCs) for education, as well as their drawbacks, which are well known. Several studies state that the main limitations of the MOOCs are low completion and high dropout rates of participants. However, MOOCs suffer also from the lack of participant engagement, personalization, and despite the fact that several formats and types of MOOCs are reported in the literature, the majority of them contain a considerable amount of content that is mainly presented in a video format. This is in contrast to the results reported in other educational settings, where engagement and active participation are identified as success factors. We present the results of a study that involved educational experts and learning scientists giving new and interesting insights towards the conceptualization of a new design approach, the flipped MOOC, applying the flipped classroom approach to the MOOCs’ design and making use of gamification and learning analytics. We found important indications, applicable to the concept of a flipped MOOC, which entails turning MOOCs from mainly content-oriented delivery machines into personalized, interactive, and engaging learning environments. Our findings support the idea that MOOCs can be enriched by the orchestration of a flipped classroom approach in combination with the support of gamification and learning analytics.